Swimming velocity analysis using wearable inertial sensors and speedometer: a comparative study - da Silva Vieira, L. J. (University of Porto, 2023)
The speedometer is a device widely used to evaluate the speed of swimming. However, its use is dependent on some constraints, such as the possibility of evaluations only in one sense of swimming with limited distance, impossibility of analysing turns and only allowing to evaluate one athlete at a time. With the appearance and constant development of inertial units (IMUs), it is expected that these can be an alternative to the speedometer. In this sense, a study was carried out with the objective of comparing the IMU data with the data provided by a speedometer during the prone swim. Sixteen swimmers, nine males (20.3 ± 3.3 years old; 65.8 ± 11.2 kg of body mass; 1.75 ± 0.07 m of height) and seven females (18.7 ± 1.1 years old; 57.7 ± 9.1 kg of body mass; 1.61 ± 0.10 m of height) performed 4 x 25 m breaststroke at maximum speed. The participants were equipped with an IMU (GT9XActiGraph Link, Florida, USA) composed of a 3D accelerometer and a 3D gyroscope fixed to the swimmer in the sacrum and properly sealed. At the same time, an electromechanical speedometer was used, fixing the line at a central point in the swimmer's lumbar region. From a qualitative curve-profile interpretation it there was an agreement in the shape of the curves, there were differences (p<0.001) regarding the magnitude of velocity with lower values measured by the IMU. Both IVV and CV were different (p < 0.01) when extracted from both methods. There was a consistent distribution of data points between the limits of agreement (~96-97% placed inside the confidence bounds) but with a large bias detected. It can be concluded that, although the velocity curves acquired from both devices have the same profile, there is an underestimation of velocity and the distance retrieved by the IMU. Both devices showed a higher degree of agreement, but it remains a larger bias that compromise comparison.